A Novel Link between the Oxytocin Receptor Gene and Impulsivity. (15th September 2020) - Bozorgmehr, Ali; Moayedi, Razieh; Sadeghi, Bahman; Ghadirivasfi, Mohammad; Joghataei, Mohammad Taghi; Shahbazi, Ali
Highlights: Novel association between OXTR gene and impulsivity shown by gene network approach. SLC6A4 and serotoninergic synapse are the most central gene and path in impulsivity. Oxytocin and GG genotype decreased commission error and increased inhibition. Oxytocin and GG genotype resulted in lower impulsivity rate compared to GA and AA. rs2254298 and G allele may modulate the function and expression of OXTR gene. Abstract: Impulsivity includes hasty actions, social intrusiveness or premature decision-making. Neuropeptides like oxytocin alleviate haste and anxiety, and affect fear conditioning. However, no investigations have been done via gene-network based approach with cognitive and interventional genetic association studies to scrutinize the link between impulsive behavior and oxytocin. Here, interactive gene network and pathways associated with impulsivity were reconstructed, and serotonin transporter gene (SLC6A4) and serotoninergic synaptic transmission were identified as the most central gene and pathway related to impulsivity. Young healthy males received intranasal oxytocin or placebo, and impulsivity was evaluated via go/no-go test. Test performance scores then were analyzed based on commission and omission errors, response inhibition and reaction time. Blood DNA was extracted and a 761 bp intronic region in oxytocin receptor (OXTR) gene was amplified and sequenced using PCR-pyrosequencing. Employing Haploview, haplotypes and linkage disequilibrium (LD) pattern among all SNPs in the target sequence were determined based on D′ and LOD values, and rs2254298 with the highest LD was indicated as the tag SNP. Oxytocin group and participants with GG genotype showed a significantly decreased commission error and increased inhibition. This means that oxytocin alleviated impulsive behavior, and subjects with GG genotype had lower rate of impulsivity than those with GA and AA genotypes. rs2254298 may modulate the function or expression of the OXTR gene, implying that G allele may increase the expression of OXTR gene compared to A allele. We suggest that intranasal oxytocin may notably moderate impulsive behavior and tendency to make hasty or premature decisions.